Aspects of the biology of aestivation in Bulinus (Physopsis) africanus (Krauss) (Gastropoda, Pulmonata) - Heeg, J. (Jan) (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1973)
Aestivation, a period of dormancy during hot, dry conditions, is known to occur in both the Prosobranchia and the Pulmonata among freshwater Gastropoda. While there have been numerous accounts, mainly by field ecologists concerned with bilharziasis control, of the survival value of aestivation in the Gastropoda, little is known of its underlying physiological mechanisms. Results of investigations into the physiological basis of aestivation in the freshwater Prosobranchia, confined to the family Ampulariidae, have been conflicting, fundamental differences having been shown to exist between different species of the genus Pila . Only a single comprehensive study, that by von Brand and his coworkers on the planorbid snail Australorbis glabratus*, forms the basis of our knowledge of the aestivation process in the aquatic Pulmonata. In view of the conflicting results obtained in investigations on freshwater Prosobranchia, the general applicability of the findings for Australorbis glabratus to other freshwater Pulmonata was open to question. The present investigation on the planorbid snail Bulinus (Physopsis) afriaanus, a species known to be a successful aestivator, was prompted by the obvious need for a further comprehensive study on an aquatic pulmonate species . The results presented here show that aestivation in this species is a definite physiological state, characterised by a depression of the metabolic rate, which not only aids in husbanding the snails I metabolic resources. during the enforced starvation which must necessarily accompany aestivation, but also constitutes a form of resistance adaptation to the transient high temperatures which aestivating snails are bound to encounter. Loss of body water is shown to be important in initiating aestivation, but it is also the factor most likely to prove lethal during the course of aestivation. The results confirm and extend the earlier findings for Australorbis glabratus. The results are discussed in the context of our present knowledge of aestivation in other Gastropoda, both aquatic and terrestrial, and also in relation to other forms of resistance adaptation. As expected, the investigation raises more questions than it answers, thus directions for further research, arising out of the present findings, are suggested.
Keywords: Uncatalogued